Políticas públicas e igualdad de género en los servidores públicos de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Santana Molina, Katheren Liseth (2025)
The main objective of this research was to evaluate public policies and gender equality among public servants at the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. To achieve this, inductive, deductive, and analytical-synthetic methods were employed, providing a comprehensive perspective on these policies. Interviews and surveys were used as data collection techniques, ensuring the validity and reliability of the information obtained. Additionally, tools such as the Servqual model, Likert scale, and Google Forms were applied, allowing for the identification of key findings. The research results indicate that, although the institution implements gender equality policies, these have not had a significant impact on public servants. While 66% affirm that the policies are disseminated, deficiencies persist in their communication and application. Furthermore, many public servants question the effectiveness of these policies in eliminating workplace inequalities. It is necessary to improve dissemination, establish impact evaluations, and create concrete actions to promote gender equity.